Two modes of amnesia: complexity in postcolonial Namibia - Reinhart Kössler (Acta Academica, 2015)
From text: Public commemoration of past atrocity, mass crime and particularly genocide has drawn attention both in the public realm and in scholarly debate, meeting general acceptance in recent years. However, the seeming opposite has also been advocated – forgetting. Variously, such forgetting is presented as a wiser approach in contradistinction to painstaking and evasive truth-seeking. Taking this tendency as a point of departure, I discuss here two cases that seem relevant to what might be called a strategy of amnesia, both relating to Namibia: (1) reference to the genocide perpetrated by the German colonial army in 1904-08, both in post-World War II (West) Germany and in the independent postcolony, and (2) the debates and conflicts within Namibia around the gross violations of human rights committed under the auspices of SWAPO during the 1980s. Without suggesting that these cases are in any wayequivalent, I contend, however, that they are related in the minds of a fair number of Namibians and further, that there are certain connections in the ways both cases have been and are addressed within the public spheres of the two countries concerned.